Teacher Opinions on the Innovation Management Skills of School Administrators and Organizational Learning Mechanisms - Omur, Yunus Emre; Argon, Turkan (ANI YAYINCILIK, 2016)
Problem Statement: In modern society, schools, just as other institutions, are required to be innovative organizations. For this purpose, they must not only be learning organizations, they must also be innovative. In this sense, the purpose of this study is to discover the relationship between organizational learning mechanisms at schools and innovation management skills of school administrators. Purpose of the Study: The purpose of this study is to determine high school teachers' opinions of the innovation management skills of school administrators and organizational learning mechanisms at high schools. Method: The research was conducted with the relational survey model, and 272 teachers were sampled with the random sampling method. To collect the research data, the Organizational Learning Mechanisms Scale and Scale of Innovation Management in Schools were used. The data was analyzed with frequency, percentage, standard deviation, mean, and Spearman's rho correlation analyses. Findings and Results: According to the results of the research, teachers' opinions of both the organizational learning mechanisms of their schools and their administrators' innovation management skills were medium level in total and at sub-dimensions; and there is a high-level, positive, and significant relationship between teachers' opinions of organizational learning mechanisms and the innovation management skills of school administrators.
Keywords: Innovation management; organizational learning mechanisms; school administrator; teacher; PERFORMANCE; CAPACITY; CULTURE; IMPACTS; SCALE; LOOP; Education & Educational Research